2014
DOI: 10.1111/vop.12237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tiletamine–zolazepam on the intraocular pressure of the dog

Abstract: The TZ combination had no clinically significant effect on IOP of the dog. This could be an option for induction or surgical procedures in dogs with ophthalmic problems when an increase in IOP is undesirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In the present study, regardless of age, sex, and eye side, the mean IOP value for Kangal dogs measured with TonoVet ® was 17.63 ± 3.34 mmHg, which was higher than mean IOPs obtained in three studies on Beagles and similar to mean IOPs in other studies in which different breeds were used (3,9,16,17). With regard to studies using applanation tonometers, mean IOPs obtained with Tono-Pen XL ® for Beagles ranged from 12.7 ± 0.8 to 15.3 ± 1.7 mmHg in one study (10) and was found to be 15.2 ± 2.2 mmHg in another (19). Another study using Tono-Pen XL ® in Labrador Retrievers determined their mean IOP as 11.93 ± 1.59 mmHg and 12.38 ± 2.10 mmHg (12).…”
Section: Methodsmentioning
confidence: 65%
“…In the present study, regardless of age, sex, and eye side, the mean IOP value for Kangal dogs measured with TonoVet ® was 17.63 ± 3.34 mmHg, which was higher than mean IOPs obtained in three studies on Beagles and similar to mean IOPs in other studies in which different breeds were used (3,9,16,17). With regard to studies using applanation tonometers, mean IOPs obtained with Tono-Pen XL ® for Beagles ranged from 12.7 ± 0.8 to 15.3 ± 1.7 mmHg in one study (10) and was found to be 15.2 ± 2.2 mmHg in another (19). Another study using Tono-Pen XL ® in Labrador Retrievers determined their mean IOP as 11.93 ± 1.59 mmHg and 12.38 ± 2.10 mmHg (12).…”
Section: Methodsmentioning
confidence: 65%
“…IOP was measured under general anaesthesia. Tiletamine mixed with zolazepam did not have a significant effect on IOP in cats or dogs 34,35 , whereas Xylazine, especially at high doses, decreased IOP in rabbits 36,37 . Given those findings, the actual IOP might be similar to or greater than the measured IOP in this study.…”
Section: Discussionmentioning
confidence: 79%
“…The combination of tiletamine + zolazepam (Zoletil ® 50, Virbac do Brazil Indústria e Comércio Ltda, Jurubatuba, SP, Brazil), detomidine (Dormiun-V ® 1%, Agener União Saúde Animal, São Paulo, SP, Brazil), and atropine (Atropina 1% Fagra ® , Mairiporã, SO, Brazil) was administered by intramuscular injection (IM). For detomidine hydrochloride, the model dose was 0.01 mg kg-1, recommended for a 500-kg horse (HAMM et al, 1995); for atropine sulfate, 0.05 mg kg-1 was used, as indicated for a 10-kg dog (UENO et al, 1999); for tiletamine + zolazepam, the model was 5.0 mg kg-1 based on a 10-kg dog (JANG et al, 2015).…”
Section: Experimental Designmentioning
confidence: 99%